Experimental Investigations on Static, Dynamic, and Morphological Characteristics of Bamboo Fiber-Reinforced Polyester Composites - N. Santhosh; B. A. Praveena; H. V. Srikanth; Santosh Angadi; Amaresh Gunge; M. Rudra Naik; G. Shankar; K. Ramesha; G. Ravichandran (International Journal of Polymer Science)
The use of natural fiber-reinforced polymer composites has increased over a period of time, majorly due to the ecosustainability and biodegradability of the composites. Among several grades of natural fibers, bamboo fibers offer numerous environmental and cost benefits and possess excellent mechanical characteristics. The superior properties of the bamboo fibers have triggered the research interests in the domain of bamboo fiber-reinforced polymer composites. Among the polymers, polyesters are long chain molecules made up of atoms arranged in various ways with other elements to form the basic building blocks of a polymeric chain. Polyester is being increasingly employed in today’s industrial products due to its inherent advantages. As a result, based on the potential properties of bamboo fibers as reinforcing materials and polyester resin as matrix material, the biocomposites are synthesized by hand lay-up technique and the specimens cut as per the standard dimensions and subjected to mechanical investigations, vibration, and morphological characterization as per the ASTM test methods. The increase in fiber weight content has enhanced flexural, tensile, and impact characteristics and improved the damping characteristics of the composite specimens. The microstructural evaluations have revealed the uniform distribution of the bamboo fibers in the resin, and the morphological studies of the fractured specimens have revealed that the fracture is majorly due to the matrix cracks rather than the fiber debonding, which is a major attribute ascertaining the strong coherent strengthening mechanism brought about by the inclusion of bamboo fiber in the polyester resin.